IMPLEMENTASI SISTEM INFORMASI MANAJEMEN DALAM APLIKASI MY UNPAM SEBAGAI SARANA INFORMASI DI UNIVERSITAS PAMULANG - Syaima; Rayhan Fathansyah Mubina; Ratna Dewi Setiawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to analyze the implementation of the Management Information System (MIS) in the My Unpam Application as an information tool for students at Pamulang University. MIS is an essential part of data management and decision-making in organizations, including educational institutions. The My Unpam application integrates information technology with campus operational activities, such as access to academic information, grades, schedules, and administration. Through a qualitative method using a literature study, this research finds that the My Unpam application facilitates information access, improves campus operational efficiency, and supports academic decision-making. From observations of previous journals, it shows that this application significantly helps in real-time information access, reduces reliance on manual processes, and accelerates communication between the campus and students. However, challenges such as technical issues and a lack of socialization of new features still need to be addressed to improve user experience. In conclusion, the implementation of My Unpam has successfully supported the operational efficiency of Pamulang University and serves as an example of MIS application in an academic environment. Keywords: Management Information System, My Unpam, academic application, operational efficiency.